Overexpression of the Starch Phosphorylase-Like Gene (PHO3) in Lotus japonicus has a Profound Effect on the Growth of Plants and Reduction of Transitory Starch Accumulation - Qin, Shanshan; Tang, Yuehui; Chen, Yaping; Wu, Pingzhi; Li, Meiru; Wu, Guojiang; Jiang, Huawu (Frontiers in Plant Science, 2016)
Two isoforms of starch phosphorylase (PHO; EC 2.4.1.1), plastidic PHO1 and cytosolic PHO2, have been found in all plants studied to date. Another starch phosphorylase-like gene, PHO3, which is an ortholog of Chlamydomonas PHOB, has been detected in some plant lineages. In this study, we identified three PHO isoform (LjPHO) genes in the Lotus japonicus genome. Expression of the LjPHO3 gene was observed in all tissues tested in L. japonicus, and the LjPHO3 protein was located in the chloroplast. Overexpression of LjPHO3 in L. japonicus resulted in a drastic decline in starch granule sizes and starch content in leaves. The LjPHO3 overexpression transgenic seedlings were smaller, and showed decreased pollen fertility and seed set rate. Our results suggest that LjPHO3 may participate in transitory starch metabolism in L. japonicus leaves, but its catalytic properties remain to be studied.